Skin color-specific and spectrally-selective naked-eye dosimetry of UVA, B and C radiations - Wenyue Zou (Nature Portfolio, 2018)
Current ultraviolet (UV) sensors cannot differentiate between UVA, B and C, each of which has a remarkably different impact on human health. Here the authors show spectrally-selective colorimetric monitoring of ultraviolet radiations by developing a photoelectrochromic ink that consists of a multiredox polyoxometalate and an e– donor.